2022
DOI: 10.3390/nu14132636
|View full text |Cite
|
Sign up to set email alerts
|

Broussonetia papyrifera Polysaccharide Alleviated Acetaminophen-Induced Liver Injury by Regulating the Intestinal Flora

Abstract: Liver injury caused by an overdose of acetaminophen (APAP) is a major public health problem. This study aimed to evaluate the effects of Broussonetia papyrifera polysaccharide (BPP) on liver injury and intestinal flora induced by APAP. The results showed that BPP could protect against APAP-induced liver injury, alleviate liver apoptosis, improve antioxidant capacity and enhance the liver’s detoxification ability to APAP. At the same time, BPP improved the intestinal flora disorder caused by APAP. More importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…In this study, after the administration of L. plantarum NKK20, we found that the concentrations of the three SCFAs (acetic acid, propionic acid, and butyric acid) significantly increased, while the concentrations of multiple secondary bile acids significantly decreased, which may be related to a decrease in the abundance of Pseudomonas and Turicibacter and an increase in the abundance of Akkermansia in mice. According to the axis principle of “intestinal microbiota—metabolite—immunity”, during gastrointestinal transit, SCFAs are metabolites of intestinal bacteria that enter the bloodstream and play an anti-inflammatory and liver-protective role [ 44 , 45 ]. They are produced by anaerobic bacteria in the intestinal tract that ferment dietary fiber incapable of being digested or absorbed by human beings in the colon segment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, after the administration of L. plantarum NKK20, we found that the concentrations of the three SCFAs (acetic acid, propionic acid, and butyric acid) significantly increased, while the concentrations of multiple secondary bile acids significantly decreased, which may be related to a decrease in the abundance of Pseudomonas and Turicibacter and an increase in the abundance of Akkermansia in mice. According to the axis principle of “intestinal microbiota—metabolite—immunity”, during gastrointestinal transit, SCFAs are metabolites of intestinal bacteria that enter the bloodstream and play an anti-inflammatory and liver-protective role [ 44 , 45 ]. They are produced by anaerobic bacteria in the intestinal tract that ferment dietary fiber incapable of being digested or absorbed by human beings in the colon segment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This extracted part of the BP and/or the administration method could be the underlying reasons for the inconsistent results found in our study. In another study, different dosages of polysaccharides extracted from BP leaves (100 mg/kg/d, 200 mg/kg/d, and 400 mg/kg/d) were orally administered to KU mice, showing a dose-dependent mitigation of acetaminophen-induced liver damage and restoration of the downregulated gene expression of Nrf2 and its downstream target genes in the liver, signifying the antioxidant benefits of BP polysaccharides (BPP) ( Xu et al., 2022 ). The specific cause of the differences observed in our study, whether related to the active compounds within the BP leaf extract and/or organ-specific targets, remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…The specific cause of the differences observed in our study, whether related to the active compounds within the BP leaf extract and/or organ-specific targets, remains ambiguous. The hepatoprotective effect of BPP may be attributed to the metabolic effects of the intestinal microbiota ( Xu et al., 2022 ). Intestinal microorganisms may interact with phytochemicals within BP extracts, exerting direct or indirect effects on the health of the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, due to the characteristics of its growing environment, the B. papyrifera also has a strong ability to tolerate a variety of unfavorable environments, such as drought, salt, and heavy metals [7][8][9]. Currently, research on B. papyrifera focuses on their breeding [10], physiological characteristics [11], medicinal [12], and pasture values [13], but less research has been performed on the molecular mechanisms of their stress tolerance. As a pioneer tree species widely cultivated in harsh environments, stress resistance is a hotspot in molecular biology research in B. papyrifera [14].…”
Section: Introductionmentioning
confidence: 99%